THE USE OF CEPAT MAHIR APPLICATION TO IMPROVE STUDENTS ENGLISH VOCABULARY MASTERY - Siregar, Intan (Faculty of Tarbiyah nad Teacher Training, 2024)
The objective of this research was to know the student’s english vocabulary mastery using Cepat Mahir Application better that using U-Dictionary application. The population of this research was the first grade of MAN Asahan. The sample were taken by using purposiv sampling technique. The sample of this research were X-3 that consist of 25 students as group A and X-6 that consist of 25 students as group B. this research employed quasi-experimental design. This type of research involves two classes. The data collection technique in this research was using pre-test, treatmen, and post-test. The results of this study indicate that the students English vocabulary was improving by using Cepat Mahir Application. This is evidence by the average score of using Cepat Mahir Application was 40.60 during the pre-test and 95.40 during the post-test. Meanwhile, using U-Dictionary was 52.80 during the pre-test and 74.40 during the post-test. There is a significant difference between using Cepat Mahir Application and using U-Dictionary Application.